1972
DOI: 10.1136/jcp.25.3.240
|View full text |Cite
|
Sign up to set email alerts
|

Histological Hashimoto's disease in a benign cystic ovarian teratoma

Abstract: A case of Hashimoto's disease of the thyroid component of a benign cystic ovarian teratoma is reported, unassociated with previous neck surgery. Three hundred and fifteen cases of ovarian teratomata were reviewed to determine the incidence of this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…Although SO can be detected at any age even in childhood, it is mostly observed in the reproductive age (16). In the recent report, the patient was in a reproductive age, which is similar to other previous evaluations (8,9,(13)(14)(15). However, some reports of the ovarian stroma are available in the 5th and 6th years of life or under 20 years (8,9,15).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although SO can be detected at any age even in childhood, it is mostly observed in the reproductive age (16). In the recent report, the patient was in a reproductive age, which is similar to other previous evaluations (8,9,(13)(14)(15). However, some reports of the ovarian stroma are available in the 5th and 6th years of life or under 20 years (8,9,15).…”
Section: Discussionsupporting
confidence: 83%
“…In half of the patients, ovarian tumors may be detected accidentally on ultrasound. Although the diagnostic criteria for SO is based on the histologic appearance of the ovarian sample, it is sometimes necessary to determine the origin of the cell by immunohistochemistry staining for thyroglobulin (13). In the recent report which was similar to previous investigations (8,9,(13)(14)(15), the probability of a dermoid cyst was noted in the sonographic report, which was finally diagnosed as SO.…”
Section: Discussionmentioning
confidence: 93%
“…Although many diseases of thyroid tissue can be seen in ovarian teratomas, Hashimoto's thyroiditis is very rare and a few cases have been reported in the literature. [12345] Hashimoto's thyroiditis in an ovarian mature cystic teratoma and thyroid papillary carcinoma derived on this ground have previously been reported in literature with only one case, and our case is presented as the second case.…”
Section: Introductionmentioning
confidence: 60%
“…None of these cases have been mentioned about Hashimoto's disease. In a study of 315 ovarian teratomas, Watson[4] reported 17 cases of thyroid tissue and only 1 case of Hashimoto's disease, in which antithyroid antibodies were found to be negative. Thyroid papillary carcinoma arising in ovarian teratoma which has Hashimoto's thyroiditis has been reported in literature only in one case.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of Hashimoto's disease in a bilateral mature cystic teratoma is a very rare phenomenon, with few cases reported in literature till date (2,3). We report this case for its rarity.…”
Section: Introductionmentioning
confidence: 82%